Allogeneic Bone Marrow Mesenchymal Stem Cell Transplantation for Periodontal Regeneration. (February 2014) - Du, J.; Shan, Z.; Ma, P.; Wang, S.; Fan, Z.
In this study, we investigated the possibility of using local administration of allogeneic bone marrow mesenchymal stem cells (BMMSCs) to induce tissue regeneration in periodontal defects in a rat model of periodontitis. BMMSCs isolated from rats were mixed with 0.9% NaCl solution and injected into periodontal defects. Control groups were 0.9% NaCl solution or left untreated. The clinical assessments, x-rays, and histological examinations were used to evaluate the effect. At 12 wks post-transplantation, quantitative analysis revealed average probing bone loss values of 1.2 ± 0.19, 1.6 ± 0.2, and 1.7 ± 0.14; the bone regeneration rate was 53%, 45%, and 44% in the BMMSC+NaCl group, NaCl group, and untreated group, respectively. The clinical assessments, x-rays, and histological examinations revealed significant periodontal tissue regeneration in the BMMSC injection group, compared with the control groups. The ELISA results showed that TNFα, IFNγ, and IL1β were 2, 674.88 ± 102.77 pg/mL vs . 3, 422.1 ± 51.98 pg/mL, 609.85 ± 25.5 pg/mL vs . 803.79 ± 33.85 pg/mL, and 1, 038.46 ± 76.29 pg/mL vs . 1, 175.26 ± 105.55 pg/mL in the BMMSC+NaCl group and NaCl group, respectively, indicating that BMMSC injection inhibited the inflammatory factors TNFα, IFNγ, and IL1β. Our results indicate that local administration of BMMSCs can repair defects due to periodontitis, exerting anti-inflammatory and immunomodulatory functions.